O pioneers! - Cather, Willa 1873-1947.; Kraus, Chris (New York Barnes & Noble Classics, 2003)
The Bergsons, a Swedish family of settlers in Nebraska, overcome drought and other disasters, and due to the courage of Alexandra, build a prosperous farm.
Originally published in 1913.
Keywords: Brothers and sisters -- Fiction; Swedish Americans -- Fiction; Women immigrants -- Fiction; Women pioneers -- Fiction; Women farmers -- Fiction; Farm life -- Fiction; Nebraska -- Fiction